The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11239-012-0734-6
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic gene polymorphisms and plasma factors in young north Indian survivors of acute myocardial infarction

Abstract: The aim of this study was to evaluate the association of prothrombotic gene polymorphisms [factor V Leiden (FVL) 1691GA, factor VII (FVII) 10976GA, FVII HVR4, platelet membrane glycoproteins GP1BA 1018CT, GP1BA VNTR, integrin ITGB3 1565TC, integrin ITGA2 807CT and methylenetetrahydrofolate reductase (MTHFR) 677C/T], plasma factors (fibrinogen and homocysteine) and traditional risk factors with acute myocardial infarction (AMI) in 184 patients ≤ 40 years of age and 350 controls (≤ 40 years) from north India. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…Further subgroup analysis based on comparison of the PlA1/A1 versus PlA2/A2 genotype failed to show a significant association ( n  = 23,836; OR 1.023, 95% CI 0.877–1.192; p = 0.774) [70]–[72], [81], [82], [86][91], [95], [98][100], [102]–[104], [106]–[108], [111][114], [116], [117], [120], [122], [124], [128] (Figure 3); however, within this analysis, the number of subjects with the PlA2/A2 genotype was small, consisting of 333 cases and 1,504 controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further subgroup analysis based on comparison of the PlA1/A1 versus PlA2/A2 genotype failed to show a significant association ( n  = 23,836; OR 1.023, 95% CI 0.877–1.192; p = 0.774) [70]–[72], [81], [82], [86][91], [95], [98][100], [102]–[104], [106]–[108], [111][114], [116], [117], [120], [122], [124], [128] (Figure 3); however, within this analysis, the number of subjects with the PlA2/A2 genotype was small, consisting of 333 cases and 1,504 controls.…”
Section: Resultsmentioning
confidence: 99%
“…For subjects ≤45 years old, carriage of the PlA2 allele produced a pooled OR for MI of 1.205 ( n  = 9,547; 95% CI 1.067–1.360; p = 0.003) with significant heterogeneity (I 2  = 70.3%, p<0.001), and analysis using the random-effects model again increased the level of association (OR 1.356, 95% CI 1.044–1.762; p = 0.022) [72], [82], [84], [86], [91], [97], [107], [116], [121][123]. Significant heterogeneity and an increased level of association as compared with the total population were also observed using the random-effects model for the ≤55 and ≤65 year-old subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…The causes of this ethnic predisposition to CAD are likely to be multi-factorial ie interaction between genetic and environmental factors. The role of inherited predisposition to coronary thrombosis is limited to certain genetic factors as shown by a recent study [23] in young north Indian survivors of AMI. More importantly, several studies [19][20][21][22] have shown that Indians are prone to developing metabolic abnormalities at a lower BMI and lower waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…CAD is caused by a thrombotic occlusion of coronary arteries triggered by atherosclerotic plaque disruption, resulting in an activation of coagulation processes [4]. It is a complex, multifactorial, and polygenic disorder that involves an interaction between genetic predisposition and environmental factors [5]. It has been shown that traditional risk factors, including diet, obesity, diabetes, hypertension, dyslipidemia, inflammation, smoking, and alcohol consumption, allow the prediction of only about 50% of the absolute risk of a cardiovascular event in individual patients [6,7], and the remaining risk is attributed to genetic influences [8].…”
Section: Introductionmentioning
confidence: 99%